Multikultural dalam Perspektif Alquran - Heru Suparman (Institut Agama Islam Negeri (IAIN) Curup, 2017)
Findings of the research suggest that the views or reviews of the Qur'an about multicultura do not against the Islamic teachings at any rate, especially the Qur'an as the source of Islamic law. The diversity that exist has in fact become intellectual property to be studied, as the Qur'an explains it. Through multicultural education, it is expected that every individual and/or every group be acceptance and appreciate toward differences among them, live said by said in harmony in order to establish a peaceful and properous nation